IMPACT OF INFLATION AND PER CAPITA INCOME ON CONSUMPTION EXPENDITURE IN ECOWAS - KEHINDE, OGUNBADEJO HUSSAIN; BALOGUN, WAKILA OLABISI; OLADIMEJI, AGBABIAKA KAMOR (JOURNAL OF ECONOMICS AND ALLIED RESEARCH, 2025)
The study used advanced auto regressive distributed lag to examine the relationship between consumer expenditure, inflation rate, and per capita income in nine ECOWAS countries from 1991 to 2023. It finds a cointegration link between GDP per capita, inflation rate, and consumption spending. In the long run, consumption is positively impacted by inflation and income in eight ECOWAS countries while in the short run, high inflation leads to a decrease in consumption expenditure. The study recommends that the government should keep inflation under control and encourage economic expansion, central banks and fiscal authorities must work together and policymakers should create stimulus plans or tax breaks that will boost spending and spur economic expansion.